Administration of Mycobacterium leprae rHsp65 aggravates experimental autoimmune uveitis in mice. - Eliana B Marengo; Alessandra Gonçalves Commodaro; Jean Pierre S Peron; Luciana V de Moraes; Fernanda C V Portaro; Rubens Belfort; Luiz Vicente Rizzo; Osvaldo Augusto Sant'Anna (PLoS ONE, 2009)
The 60 kDa heat shock protein family, Hsp60, constitutes an abundant and highly conserved class of molecules that are highly expressed in chronic-inflammatory and autoimmune processes. Experimental autoimmune uveitis [EAU] is a T cell mediated intraocular inflammatory disease that resembles human uveitis. Mycobacterial and homologous Hsp60 peptides induces uveitis in rats, however their participation in aggravating the disease is poorly known. We here evaluate the effects of the Mycobacterium leprae Hsp65 in the development/progression of EAU and the autoimmune response against the eye through the induction of the endogenous disequilibrium by enhancing the entropy of the immunobiological system with the addition of homologous Hsp. B10.RIII mice were immunized subcutaneously with interphotoreceptor retinoid-binding protein [IRBP], followed by intraperitoneally inoculation of M. leprae recombinant Hsp65 [rHsp65]. We evaluated the proliferative response, cytokine production and the percentage of CD4(+)IL-17(+), CD4(+)IFN-gamma(+) and CD4(+)Foxp3(+) cells ex vivo, by flow cytometry. Disease severity was determined by eye histological examination and serum levels of anti-IRBP and anti-Hsp60/65 measured by ELISA. EAU scores increased in the Hsp65 group and were associated with an expansion of CD4(+)IFN-gamma(+) and CD4(+)IL-17(+) T cells, corroborating with higher levels of IFN-gamma. Our data indicate that rHsp65 is one of the managers with a significant impact over the immune response during autoimmunity, skewing it to a pathogenic state, promoting both Th1 and Th17 commitment. It seems comprehensible that the specificity and primary function of Hsp60 molecules can be considered as a potential pathogenic factor acting as a whistleblower announcing chronic-inflammatory diseases progression.